Digital Green Human Resource Management and Organisational Sustainability - Muhammad Syahrudin (Universitas Airlangga, 2026)
Background: Digital Green Human Resource Management (DGHRM) has emerged from rapid transitions in HR systems. Research on Digital Green Human Resource Management (DGHRM) remains fragmented: only 50 studies were identified between 2020 and 2025, mostly from Asian countries, with limited evidence from other regions and fragmented theoretical approaches. It pays little attention to how digitalization creates conflicting effects on sustainability. Objective: This paper systematically reviews contributions to GHRM and DGHRM by focusing on their conceptual evolution, prevailing theories, methodologies, and influence on organizational sustainability and ESG performance over the period 2020 to 2025. Method: The authors followed the PRISMA 2020 protocol and SPAR-4-SLR methodology for a Systematic Literature Review (SLR). They used set keywords for GHRM, digital HRM, and sustainability to collect publications from Scopus and Web of Science. Results: DGHRM demonstrates substantial capacity to incorporate digital tools, such as artificial intelligence, HRIS, and predictive analytics, to improve efficiency, transparency, and the quality of sustainability reporting. The persistent digital sustainability paradox is evident: while DGHRM enhances organizational sustainability performance, it simultaneously raises concerns about energy consumption, data privacy, and algorithmic bias. Conclusion: DGHRM involves connecting employee behaviours at the micro level through digital innovation to sustainable outcomes at the macro level. The Resource-Based View, the Stakeholder Theory, and Dynamic Capabilities further advance conceptual clarity, and it would be beneficial for future research to connect these theories. Future research should also include more ethical governance, methodological pluralism, and geographical balance. Keywords: digital GHRM; employee green behaviour; ESG, sustainable growth, SDGs.